2021
DOI: 10.1002/ccr3.5118
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiographic success of injection‐molded 2‐piece zirconia implants submitted to immediate loading: A 12‐month report of two cases

Abstract: This case report describes the treatment of two patients who presented with single edentulous sites in the region of upper premolars and were rehabilitated through the placement of injection‐molded 2‐piece zirconia implants and immediate single crowns. Three months after surgery, definitive prostheses were confectioned through digital workflow. Both patients were followed for 12 months during which clinical and radiographic implant success were observed, concerning implant stability, absence of peri‐implantiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…Also, in vitro studies have shown comparable or even better soft tissue behavior around zirconia discs, with better healing responses, which might positively affect peri-implant soft tissue health [24]. the clinical report suggested that treatment with a two-piece zirconia implant and zirconia prosthetic components is a reliable and successful alternative to single elements and immediate rehabilitation, with predictable short-term results about peri-implant health and aesthetics [27].…”
Section: Discussionmentioning
confidence: 99%
“…Also, in vitro studies have shown comparable or even better soft tissue behavior around zirconia discs, with better healing responses, which might positively affect peri-implant soft tissue health [24]. the clinical report suggested that treatment with a two-piece zirconia implant and zirconia prosthetic components is a reliable and successful alternative to single elements and immediate rehabilitation, with predictable short-term results about peri-implant health and aesthetics [27].…”
Section: Discussionmentioning
confidence: 99%